Fasciola hepatica: epidemiology, perspectives in the diagnostic and the use of geoprocessing systems for prevalence studies - Marcos André Aleixo (Semina: Ciências Agrárias, 2015)
Fasciola hepatica is a parasite that is located in the liver of ruminants with the possibility to infect horses, pigs and humans. The parasite belongs to the Trematoda class, and it is the agent causing the disease called fasciolosis. This disease occurs mainly in temperate regions where climate favors the development of the organism. These conditions must facilitate the development of the intermediate host, the snail of the genus Lymnaea . The infection in domestic animals can lead to decrease in production and control is made by using triclabendazole. Triclabendazole resistance in F. hepatica has been reported worldwide including in Brazil. Another concern is the increase number of human cases with the consumption of contaminated vegetables in regions where sanitation is inadequate together with the presence of infected animals and the absence of ef¿cient control methods. The knowledge of the epidemiology of animal fasciolosis, including their occurrence, distribution and monitoring with techniques such as PCR and ELISA is reaching a new level with the usage of the Geographic Information System. The objective is to use new technologies for early fasciolosis diagnostic, as well as, to develop geoprocessing technics that could allow the determination of its prevalence and the evolution of clinical cases in animals before hand. This review paper provides an overview of F. hepatica , covering the aspects listed above, including original data.